The First Response of Family to Patient with Heart Attack in Banjarese Community South Kalimantan: A Phenomenological Study - Hamzah; Solikin; Mohtar, M. Sobirin; Budiyarti, Yuliani (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
Family first response in patients with heart attacks is very important in increasing patient safety. Friedman's familiy theory views that the family has a major role and function indecide the prompt and appropriate course of action. Orem's Wholly Compensatory System Theory looked at that familymust provide partial assistance when a family member is sick. Theory Cultural care Leininger looked at that family tend to maintain their culture when doing help. Indonesia, especially in Banjarmasin, has different social and cultural conditions so that the experience of making its first response will of course also be different. This study aims to explore the family experience of the first response to patients with heart attacks. This study used a qualitative method with a phenomenological study approach to 8 participants from Banjar community in South Kalimantan with purposive sampling technique. Collecting data using in-depth interviews with a tape recorder and field notes. The method of analysis uses Creswell. There are 6 themes found namely (1) The initial understanding of a family about heart attack is in the form of menyamak or angin duduk, (2) The family's first action in a patient with an attackheart in the form of cabut angin, (3) family onset in doing his first response against attacks in the form of estimated time (4) Family delay factors in doing the first response in the form of a cause(5) The emotional response of the family in facing a heart attack such as neutral response, anxiety and shock. (6) Meaning as a helper for family members such as pride, relief and pleasure. Nurses need to rectify the culture that is in conflict with health by changing the family mindset of their understanding of diseases, especially heart attacks.